Assessing the Drivers of Profit Growth thru Total Asset Turnover, Return on Assets, Institutional Ownership and Public Share Ownership - Rifa Nur Apriliani; Devyanthi Syarif (eCo-Fin, 2026)
This study looks at how Indonesian telecom businesses' profit growth is affected by Total Asset Turnover (TATO), Return on Assets (ROA), Institutional Ownership (IO), and Public Share Ownership between 2019 and 2024. The study examines 42 financial statements from particular telecom companies using a quantitative methodology that takes a descriptive and verificative approach. Multiple linear regression analysis, the coefficient of determination test, the product moment correlation coefficient test, and traditional assumption tests, such as F-tests and t-tests for hypothesis testing, were used to assess the correlations between the variables. Version 21.0 of the SPSS software was used to process the data. TATO and PSO have a beneficial impact on profit growth, but ROA and IO have no effect, according to the incomplete test results. However, TATO, ROA, IO, and PSO collectively have a major influence on Profit Growth, according to the simultaneous test results. These results imply that while short-term profitability does not seem to be a significant determinant of profit growth in the telecommunications industry, activity ratio and ownership mix do.